Phenylephrine-Induced Cardiovascular Changes in the Anesthetized Mouse: An Integrated Assessment of in vivo Hemodynamics Under Conditions of Controlled Heart Rate - Rajanathan, Rajkumar; Pedersen, Tina Myhre; Thomsen, Morten B.; Botker, Hans Erik; Matchkov, Vladimir V. (Frontiers in Physiology, 2022)
Objective: Investigating the cardiovascular system is challenging due to its complex regulation by humoral and neuronal factors. Despite this complexity, many existing research methods are limited to the assessment of a few parameters leading to an incomplete characterization of cardiovascular function. Thus, we aim to establish a murine in vivo model for integrated assessment of the cardiovascular system under conditions of controlled heart rate. Utilizing this model, we assessed blood pressure, cardiac output, stroke volume, total peripheral resistance, and electrocardiogram (ECG). Hypothesis: We hypothesize that i) our in vivo model can be utilized to investigate cardiac and vascular responses to pharmacological intervention with the α1-agonist phenylephrine, and ii) we can study cardiovascular function during artificial pacing of the heart, modulating cardiac function without a direct vascular effect. Methods: We included 12 mice that were randomly assigned to either vehicle or phenylephrine intervention through intraperitoneal administration. Mice were anesthetized with isoflurane and intubated endotracheally for mechanical ventilation. We measured blood pressure via a solid-state catheter in the aortic arch, blood flow via a probe on the ascending aorta, and ECG from needle electrodes on the extremities. Right atrium was electrically paced at a frequency ranging from 10 to 11.3 Hz before and after either vehicle or phenylephrine administration. Results: Phenylephrine significantly increased blood pressure, stroke volume, and total peripheral resistance compared to the vehicle group. Moreover, heart rate was significantly decreased following phenylephrine administration. Pacing significantly decreased stroke volume and cardiac output both prior to and after drug administration. However, phenylephrine-induced changes in blood pressure and total peripheral resistance were maintained with increasing pacing frequencies compared to the vehicle group. Total peripheral resistance was not significantly altered with increasing pacing frequencies suggesting that the effect of phenylephrine is primarily of vascular origin. Conclusion: In conclusion, this in vivo murine model is capable of distinguishing between changes in peripheral vascular and cardiac functions. This study underlines the primary effect of phenylephrine on vascular function with secondary changes to cardiac function. Hence, this in vivo model is useful for the integrated assessment of the cardiovascular system.